THE FIRST 6TH-MONTH NUTRITIONAL STATUS OF A FULL-TERM CHILD IN EXCLUSIVE BREASTFEEDING: A LITERATURE REVIEW - Relisa Nuris Shifa; Sulistiawati; Endyka Erye Frety; Astika Gita Ningrum (SEAJOM: The Southeast Asia Journal of Midwifery, 2021)
Background: The first six months after birth are part of the first 1000 days, a golden period for child development. In this period, the child needed proper nutrition to support optimal development and as nutrition programming. WHO recommends exclusive breastfeeding (EBF) for the first 6th-month. Adequacy of nutrition and optimal growth can be assessed using the nutritional status. Aim: This study analyzes the relationship between EBF for the first 6 months with the nutritional status of a full-term infant aged 0-6 months. The nutritional status assessed using anthropometric measurements and child growth standards. Methods: This type of literature review research uses the PRISMA, PICO, and Boolean Operator methods. The research question with PICO standard "What is a relationship between exclusive breastfeeding practice and nutritional status of children aged 0-6 months?". Relevant literature was obtained from 8 databases: Scopus, Portal Garuda, Proquest, Mendeley, Pubmed, Oxford, Science Direct, and Sage. Literature was limited to the last 10 years. There are 6 relevant pieces of literature included for review. The literature quality assessment uses a quantitative study quality assessment tool released by the EPHPP (Effective Public Health Practice Project) and produces 5 pieces of literature worthy of review. Results: From 5 kinds of literature, there were various indicators of nutritional status such as weight-for-age (WAZ), length-for-age (LAZ), weight-for-length (WLZ), Body Mass Index (BMI)-for-age, and head circumference (HC)-for-age. The results were dominated by insignificant results, except the HC-for-age indicator stated that there were significant results. The author explores the causes of insignificant results. Explores based on the indicators that include in studies, the information based on studies, and the possible consequences that adjusted to the data based on the studies. The Author found that the mother plays an important role in the production and provision of breast milk. The quality of breastmilk depends on the mother, also how she gives it to their infant. It has to be based on the WHO recommendation. Conclusion: The result of these studies affirms that EBF didn't significantly affect the indicators of WAZ, LAZ, WLZ, and BMI-for-age, but significantly affected the head circumference-for-age indicator.